2022
DOI: 10.34172/jhp.2022.21
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective activities of acai berries (Euterpe sp.): A review

Abstract: Dietary interventions rich in fruits and vegetables in aging people can reverse or mitigate age-related cognitive declines, delay the onset of neurodegenerative diseases (NDDs), and provide long-term health dividends. The novel food, popularly known as "Acai", is a berry belonging to the Euterpe genus of tropical palms trees and natively found in South America. Euterpe oleracea has been given much attention among scientists due to its high antioxidant capacity compared to other fruits and berries. Additionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 108 publications
(150 reference statements)
0
10
0
1
Order By: Relevance
“…The composition of açai pulp has also been studied, and it contains a number of phytochemicals that have physiological activity. Numerous studies have demonstrated the neuroprotective properties of açai berries [ 30 ]. The causes of many of these diseases are multifactorial, including oxidative stress, chronic neuroinflammation, excitotoxicity, mitochondrial dysfunction, alteration in autophagy, abnormal protein accumulation in brain tissues, and other cellular aetiologias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition of açai pulp has also been studied, and it contains a number of phytochemicals that have physiological activity. Numerous studies have demonstrated the neuroprotective properties of açai berries [ 30 ]. The causes of many of these diseases are multifactorial, including oxidative stress, chronic neuroinflammation, excitotoxicity, mitochondrial dysfunction, alteration in autophagy, abnormal protein accumulation in brain tissues, and other cellular aetiologias.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, phytochemical analyses revealed that the açai berry contains a significant amount of luteolin, quercetin, dihydrokaempferol, and chrysoerial, among other polyphenolics, as well as a variety of anthocyanins, including cyanidin, delphinidin, malvidin, pelargonidin, and peonidin. Açai fruit pulp included five different types of carotenoids, including carotene, lycopene, astaxanthin, lutein, and zeaxanthin [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extratos ricos em polifenóis apresentam o potencial de proteger as células endoteliais vasculares humanas contra o estresse oxidativo e inflamação, além da capacidade neuroprotetora (MOLYNEUX, 2004;OLIVEIRA et al, 2015;ALNASSER, 2022). Ambas as espécies de açaís apresentam valores de fenólicos e antocianinas totais que foram positivamente correlacionados com uma elevada atividade antioxidante (OLIVEIRA et al, 2019).…”
Section: Introductionunclassified
“…Additionally, phytochemical tests showed that açai fruit contains considerable amounts of anthocyanins, such as cyanidin, delphinidin, malvidin, pelargonidin, and peonidin, as well as other polyphenolics, such as luteolin, quercetin, dihydrokaempferol, and chrysoerial. Five forms of carotenoids—carotene, lycopene, astaxanthin, lutein, and zeaxanthin—are found in the pulp of açai fruit [ 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%